Typhonium flagelliforme decreases tyrosine kinase and Ki67 expression in mice - Chodidjah Chodidjah; Edi Dharmana; Hardhono Susanto; Sarjadi Sarjadi (Universa Medicina, 2013)
Background Worldwide, breast cancer is the most frequent cancer in women after lung cancer. Treatments include surgery, radiation, immunotherapy and chemotherapy, but are not effective. Tyrosine kinase and Ki67 protein are markers of proliferation. Typhonium flagelliforme ethanol extract (TFEE) has been shown to inhibit proliferation of Michigan Cancer Foundation-7 (MCF7) cells in culture. The aim of the present study was to examine the effect of administration of TFEE on tyrosine kinase and Ki67 expression in mice. Methods This experimental study using post test randomized design with control group was conducted in 24 tumor-bearing CH3 mice. They were randomly divided into 4 groups, consisting of one control and 3 treatment groups (TI, T2, T3) treated daily for 30 days with 0.2 ml TFEE at dosages of 200, 400, and 800 mg/kgBW, respectively. On day 31 the tumor tissues were collected and their tyrosine kinase and Ki67 expression were levels assessed using ELISA and immunohistochemical staining, respectively. Tyrosine kinase and Ki67 expression levels were analyzed, respectively using Kruskal Wallis test and one-way Anova followed by Bonferroni post hoc test. Results Mean tyrosine kinase level was highest in the control group, followed by T3, T2 and T1 (p=0.019). Mean level of Ki 67 expression was highest in the control group, followed by T2, T3 and T1 (p=0.000). Conclussions Oral administration of TFEE at a dose of 200 mg/kgBW decreases tyrosine kinase levels and Ki 67 expression.